2014
DOI: 10.1111/tpj.12531
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculate fruit gene Tu encodes a C2H2 zinc finger protein that is required for the warty fruit phenotype in cucumber (Cucumis sativus L.)

Abstract: SUMMARYCucumber fruits that have tubercules and spines (trichomes) are known to possess a warty (Wty) phenotype. In this study, the tuberculate fruit gene Tu was identified by map-based cloning, and was found to encode a transcription factor (TF) with a single C 2 H 2 zinc finger domain. Tu was identified in all 38 Wty lines examined, and was completely absent from all 56 non-warty (nWty) lines. Cucumber plants transgenic for Tu (TCP) revealed that Tu was required for the Wty fruit phenotype. Subcellular local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 46 publications
1
87
0
Order By: Relevance
“…The major-effect QTL for fruit wart size, fws5, was resolved into a single bin C5B506 in all four trials ( Figure 1D); it was 520 kb in length and harbored the cloned fruit wart gene Tu (Yang et al, 2014). The major QTL for uniform immature fruit color u5 was also mapped to the bin C5B506 in all three trials ( Figure 1D); it contained the 313.2-kb interval previously determined using 800 segregants (Yang et al, 2013).…”
Section: Molecular Plantmentioning
confidence: 99%
“…The major-effect QTL for fruit wart size, fws5, was resolved into a single bin C5B506 in all four trials ( Figure 1D); it was 520 kb in length and harbored the cloned fruit wart gene Tu (Yang et al, 2014). The major QTL for uniform immature fruit color u5 was also mapped to the bin C5B506 in all three trials ( Figure 1D); it contained the 313.2-kb interval previously determined using 800 segregants (Yang et al, 2013).…”
Section: Molecular Plantmentioning
confidence: 99%
“…Seven signals were significantly associated with the trait (P < 1e 28 ) (Supplemental Figure 6), including one that resided within the genetically mapped tu region on chromosome 5, which has previously been reported to determine the formation of fruit tubercules (Zhang et al, 2010a). This SV involves the deletion of the entire tu gene (Csa5G577350, encoding a C 2 H 2 type zinc finger transcription factor) (Yang et al, 2014) in five Eurasian cucumber lines (Supplemental Figure 6). In addition, our analysis indicated that this deletion is caused by a microhomolog (AATT) at the breakpoints (Supplemental Figure 6), elucidating the formation of tu, a null allele explored by breeders for developing cultivars for European and US supermarkets where cucumbers are generally packed in plastic for transportation and longer shelf-life (and thus must be spineless).…”
Section: Functional Impact Of Cucumber Svsmentioning
confidence: 99%
“…Warty phenotype occurs when trichromes are combined with tubercules. The nWty fuits against Wty, are smoother, better in taste and possess lower pesticide residues, they are easy to wash, transport and store [16,33]. The map-based cloning study of nWty and Wt cucumber lines revealed presence of Tu (tuberculate) gene in all warty fruits, which seems that this gene is needed for warty fruits phenotype formation.…”
Section: The Utility Of Ngs In Mapping Technologymentioning
confidence: 94%